Asymmetric division: An antitumor player?. (3rd July 2016) - Wang, Lihua; Bu, Pengcheng; Shen, Xiling
ABSTRACT: miR-34a-mediated asymmetric cell division reins in excessive stem cell expansion during tissue regeneration in the intestine and colon. Loss of miR-34a switches asymmetric division to symmetric division and enhances stem cell proliferation. Asymmetric division also occurs in the early stages of colon cancer stem cells. Mechanistically, miR-34a, Numb, and Notch form a feed-forward loop that specifies cell fate when stem cells divide.